Synthesis and characterization of branched fullerene-terminated poly(ethylene glycol)s. Issue 7 (20th November 2014) - Yau, Hin Chun; Bayazit, Mustafa K.; Gaffney, Piers R. J.; Livingston, Andrew G.; Steinke, Joachim H. G.; Shaffer, Milo S. P.
Abstract : Direct transesterification of phenyl-C61 -butyric acid methyl ester with polyethylene glycols produces a range of multiple fullerene species. The use of a monodispersed PEG core allows isolation of a pure fully substituted product. Abstract : Poly(ethylene glycol) [1, PEG∼4 (OH)2, M n ∼ 200], glycerol ethoxylate [2, PEG∼21 (OH)3, M n ∼ 1000] and pentaerythritol ethoxylate [3, PEG∼15 (OH)4, M n ∼ 797] react directly with phenyl-C61 -butyric acid methyl ester (PCBM), in the presence of dibutyltinoxide (DBTO) catalyst at 140 °C, to give a mixture of fullerene [C60 ] end-capped PEGs via transesterification. Among these PEG linkers, only PEG∼4 (OPCB)2 (4a ) (OPCB: ester oxygen linked phenyl-C61 -butyryl group) was successfully isolated from the crude product mixture in the fully end-capped form. Fully acylated PEG∼21 (OPCB)3 (5 ) and PEG∼15 (OPCB)4 (6 ) could not be separated chromatographically from incompletely reacted species due to the polydispersity in branch lengths. This purification challenge was overcome by using a monodisperse branched core, 1, 3, 5-tris(octagoloxymethyl)benzene [7, PEG24 (OH)3 ] to give a monodisperse tris-fullerene homostar, PEG24 (OPCB)3 (8 ). The structures of the bis- and tris-fullerene products were confirmed by MALDI-TOF mass spectrometry and 1 H NMR spectroscopy with supporting FTIR and UV-vis spectroscopic analysis.